2019
DOI: 10.1007/s40272-019-00325-x
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Guide to Treatment of Childhood Absence Epilepsy

Abstract: Childhood absence epilepsy (CAE) is a common pediatric epilepsy syndrome with distinct seizure semiology, electroencephalography (EEG) features, and treatment. A diagnosis of CAE can be obtained during an office visit with a careful history, physical exam including prolonged hyperventilation, and a routine EEG. The treatment of choice for CAE with absence seizures only is ethosuximide. Valproic acid and lamotrigine are also effective treatments for many patients, but when compared to ethosuximide, valproic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 64 publications
0
54
0
2
Order By: Relevance
“…There were no pronounced automatisms or myoclonia. CAE is an idiopathic, generalized epilepsy with a typical onset between 4-10 years of age (Kessler and Mcginnis, 2019). While affected children were generally believed to have a normal neurological and cognitive development, an increased risk of attention deficit and subsequent academic difficulties has been reported (Masur et al, 2013).…”
Section: Eeg-based Functional Network Analysis In Epilepsymentioning
confidence: 99%
“…There were no pronounced automatisms or myoclonia. CAE is an idiopathic, generalized epilepsy with a typical onset between 4-10 years of age (Kessler and Mcginnis, 2019). While affected children were generally believed to have a normal neurological and cognitive development, an increased risk of attention deficit and subsequent academic difficulties has been reported (Masur et al, 2013).…”
Section: Eeg-based Functional Network Analysis In Epilepsymentioning
confidence: 99%
“…Children with CAE often suffer absence seizures during which children lose consciousness and stare blankly. Children with CAE have a risk for psychosocial and behavioral comorbidities and may develop persistent absence seizures or other types of epilepsy ( Kessler and McGinnis, 2019 ). CAE mostly occurs in school-age children, ranging from 6 to 12 years of age, and the morbidity of CAE is higher in females than in males.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood absence epilepsy is considered primary generalized epilepsy. On electroencephalography (EEG), seizures are characterized by a highly recognizable pattern of generalized (bilateral, symmetric, and synchronous) 3-Hz spike and wave discharges (SWDs) ( Kessler and McGinnis, 2019 ). However, an increasing number of studies have found that CAE was more likely to have focal brain origins that were responsible for absence seizures ( Westmijse et al, 2009 ; Kim et al, 2011 ; Tenney et al, 2013 ; Rozendaal et al, 2016 ; Kokkinos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different types of seizures require the use of different antiepileptic drugs: phenobarbital and phenytoin are often used as the first choice for treating epileptic seizures [33] . And for absence seizure, ethosuximide is often used as the primary therapeutic drug [34] . As a classic antiepileptic drug, VPA has a good therapeutic effect on many types of epilepsy.…”
Section: Discussionmentioning
confidence: 99%